2014
DOI: 10.21314/jcf.2014.275
|View full text |Cite
|
Sign up to set email alerts
|

Option calibration of exponential Lévy models: confidence intervals and empirical results

Abstract: Observing prices of European put and call options, we calibrate exponential Lévy models nonparametrically. We discuss the efficient implementation of the spectral estimation procedures for Lévy models of finite jump activity as well as for self-decomposable Lévy models. Based on finite sample variances, confidence intervals are constructed for the volatility, for the drift and, pointwise, for the jump density. As demonstrated by simulations, these intervals perform well in terms of size and coverage probabilit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 23 publications
0
17
0
Order By: Relevance
“…The choice of the weight functions is discussed in [28], where also possible weight functions are given. The weight functions for all U > 0 can be obtained from w 1 σ , w 1 γ , w 1 λ and w 1 µ by rescaling:…”
Section: The Estimation Methodsmentioning
confidence: 99%
“…The choice of the weight functions is discussed in [28], where also possible weight functions are given. The weight functions for all U > 0 can be obtained from w 1 σ , w 1 γ , w 1 λ and w 1 µ by rescaling:…”
Section: The Estimation Methodsmentioning
confidence: 99%
“…In the related setting of estimation from financial option data the weight function approach has been successfully analysed and applied by Belomestny and Reiß [4]. Söhl [23] addresses testing and confidence regions for this situation in detail and Söhl and Trabs [22] apply this to financial data. Generalisations to other processes defined by their Fourier transform are possible, e.g.…”
Section: Discussion and Extensionsmentioning
confidence: 99%
“…Söhl [25] have derived confidence sets. An empirical study of the calibration methods can be found in Söhl and Trabs [26]. By arbitrage arguments the price process of an asset should be a martingale implying E[S t ] = S 0 for all t > 0.…”
Section: Observation Of Option Pricesmentioning
confidence: 99%
“…Let us finally apply the estimation method to prices of DAX options from May 29, 2008. This data set 1 has already been studied by Söhl and Trabs [26]. Fig.…”
Section: Simulations and Real Datamentioning
confidence: 99%
See 1 more Smart Citation